Exploring the importance of a usable and emotional product design from the user’s perspective - Buker, Tina; Schmitt, Teresa; Miehling, Jörg; Wartzack, Sandro (Ergonomics, 2022)
Usability and emotionality are important components of user experience. However, an equal consideration of both constructs in product design is not always possible due to sometimes competitive objectives. In order to foster a user-oriented design decision in such conflicting situations, this paper examines the general importance of both constructs and their dimensions from the user’s perspective while taking into account socio-demographic variables. Examination was realised by conducting a product independent anonymous online survey (n = 130). The findings confirm that both constructs are important, yet in a direct comparison, usability is perceived as more important than emotionality. Taking selected dimensions of both constructs into account, an intuitive, easy and learnable usage, suitability for the user's task and freedom from impairment are particularly important in terms of usability. An aesthetic and pleasurable product design as well as originality is essential in terms of emotionalit
Keywords: usability; emotional design; product design; user-centred design; empirical study